2010
DOI: 10.1016/j.seizure.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Injection of embryonic median ganglionic eminence cells or fibroblasts within the amygdala in rats kindled from the piriform cortex

Abstract: MGE cells implanted at the amygdala may control the focal component of temporolimbic seizures. This effect may be mediated by local release of GABA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A study in a rat model of kindling epilepsy also showed the efficiency of rat MGE cells for reducing seizures (Gallego et al, 2010, Table 1). Grafting E14.5 rat MGE into the amygdala following 3 days of full kindling increased thresholds for after discharges and seizures at 3–24 days post-grafting, in comparison to kindled rats receiving fibroblasts.…”
Section: Efficacy Of Primary Gaba-ergic Cell Grafts For Mediating mentioning
confidence: 94%
“…A study in a rat model of kindling epilepsy also showed the efficiency of rat MGE cells for reducing seizures (Gallego et al, 2010, Table 1). Grafting E14.5 rat MGE into the amygdala following 3 days of full kindling increased thresholds for after discharges and seizures at 3–24 days post-grafting, in comparison to kindled rats receiving fibroblasts.…”
Section: Efficacy Of Primary Gaba-ergic Cell Grafts For Mediating mentioning
confidence: 94%
“…Several evidences indicate that therapeutic benefits can be obtained by transplanting fetal GABAergic progenitors into the dentate gyrus in rodents with TLE. Recent progress in cell transplantation using the TLE model were well described (76) and, fetal hippocampal cell grafts, neuronal precursor cells from medial ganglionic eminence, and other neural stem cells (NSCs) have been tested as efficacious transplantable cells able to replace damaged hippocampal neurons in epilepsy models (77,78).…”
Section: Stem-cell Therapy And/or Neurotrophic Factors As Inducers Ofmentioning
confidence: 99%
“…As shown in Table 1 , a variety of cell types have been tested in animal models of epilepsy, including neural stem cells; human induced pluripotent stem cells; GABAergic progenitors derived from mouse or human embryonic stem cells; GABAergic precursors; striatal precursor cells (Hattiangady et al, 2008 ; Baraban et al, 2009 ; Gallego et al, 2010 ; De la Cruz et al, 2011 ; Shetty and Upadhya, 2016 ). Several studies now convincingly support the notion that some types of cells can successfully treat epilepsy in animal models.…”
Section: Cell Therapy Approaches: Direct Cell Graft Injectionmentioning
confidence: 99%